County carbon emissions in the Yangtze River Delta region: Spatial layout, dynamic evolution and spatial spillover effects - Wei, Zhongyin; Li, Jiaming; Wang, Ziyi; Zhou, Anqi; Li, Muhan (Frontiers in Environmental Science, 2022)
The Yangtze River Delta region contributes nearly 16% of the national carbon emissions and is the key area for carbon emission reduction in China. Accurately grasping the spatial evolution characteristics of carbon emissions and the interaction between counties and regions is of great practical significance for precise and collaborative carbon reduction. This study firstly explores the spatial layout and dynamic evolution characteristics of county carbon emissions in the Yangtze River Delta region from 2000 to 2018 by using spatial statistical analysis, secondly identifies the influencing factors of county carbon emissions(CAR) in the Yangtze River Delta region from dynamic and static dimensions respectively by using static and dynamic Spatial Dubin Model, and finally judges the spatial spillover effects of each factor. We find that county carbon emissions are more complex and more diverse in non-synchronous state compared to provinces and cities. The high carbon areas in the Yangtze River Delta region are concentrated in Shanghai and its neighboring cities, as well as industrial counties under the jurisdiction of other sub-core cities, which are continuously clustered towards the center. We have made some theoretical discussions on the results of the spillover effects of various factors on carbon emissions, and concluded that economic of scale(ECO) and industrial structure(IND) have a "polarization effect", population size(POP) is consistent with the Malthusian view, technological advance(TEC) has a "cumulative effect", and environmental quality(ENV) The "pollution paradise effect" is mitigated. Finally, we believe that the main unit of precise carbon reduction can take the form of "city-county" combination, and the government should implement differentiated and coordinated carbon reduction policies.